Alteration, mineralization, geochemistry and fluid inclusion investigations in Joftrud prospect area, southwest of Birjand - Omid Shareipour; Azadeh Malekzadeh Shafaroudi; Maryam Javidi Moghaddam (Journal of Economic Geology)
The Joftrud prospect area is located in the central Lut Block and 60 Km of Birjand city. The area comprises outcrops of pyroclastic (andesitic tuff), volcanic (hornblende andesite, pyroxene andesite, basaltic andesite), intrusive (diorite porphyry, monzodiorite, gabbro) rocks. Mineralization as vein-type with mostly northeast-southwest trend has formed in andesitic units. Main alterations are consist of silicified, argillic, carbonate and propylitic. Primary minerals include chalcopyrite, pyrite, and secondary minerals are consist of chrysocolla, chalcocite, covellite, azurite, malachite, goethite, and hematite. Maximum of geochemical anomalies in veins are for copper 6000 ppm, lead 2934 ppm, zinc 6904 ppm, and Au 144 ppb. Quartz-sulfide veins are formed of fluids with temperature of 265 to 408ºC and salinity of 11.1 to 19 NaCl wt.‌% equivalent. Decreasing temperature and fluid mixing by high-salinity fluid can cause metal deposition. According to the available evidence of structural control of mineralization, alterations and their narrow expansions, mineralogy, texture, fluid inclusion data and depth of formation, prospect area is similar to intermediate sulfidation deposit.